PERAN AUDIT INTERNAL DAN SISTEM PENGENDALIAN INTERNAL ATAS PENGAJUAN KREDIT TANPA AGUNAN PADA PERUSAHAAN PERBANKKAN DI INDONESIA - Sugiyanto Sugiyanto; Indra Iman Sumantri (Jurnal Akuntansi, 2019)
The purpose of this research is to find out how big the role of internal audit and internal control systems is over the filing of Indonesian Bank Loans (KTA). In this study using the Descriptive Associative Method with qualitative and quantitative data approach methods. The sample in this study were employees of internal audit and Unsecured Loans, totaling 100 respondents, for the questionnaire using the saturated sampling technique method. To find out how big the role of internal audit and internal control systems is for applying for the Indonesian banking loan KTA by testing statistics with multiple linear regression formulas analyzed with the SPSS 24.0 for windows application program. The calculation shows that the role of internal audit makes a significant contribution, while the internal control system has no influence on the application of the KTA. The role of the internal auditor gives a very strong contribution, meaning that if the audit is carried out properly, the level of fraud will be prevented earlier. Likewise with the internal control system which has a positive correlation, but in testing the hypothesis that the internal control system is not significant with the filing of the KTA, a good control system has no significant effect in detecting potential fraud in the credit application process. Keywords: Role of Internal Audit, Internal Control System and Submission of Unsecured Loans (KTA).